2019
DOI: 10.1136/bmjopen-2018-024116
|View full text |Cite
|
Sign up to set email alerts
|

Spatial barriers and the bypassing of nearby dental clinics for dental services: a secondary data analysis in Korea

Abstract: ObjectiveThis study aimed to calculate the distance patients travel to dental clinics, the rate of bypassing nearby dental clinics and the distance covered when bypassing nearby dental clinics, and explored factors associated with patients’ spatial access to dental clinics.DesignA secondary data analysis.SettingKorea Health Panel.ParticipantsWe included users of dental care services from 2008 to 2011. A total of 2375 patients and 15 978 dental visits were analysed.Primary outcome measuresKorea Health Panel dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Despite a large catchment zone, majority of the population do not seek adequate dental services provided. Hosung Shin and Han-A Cho [11] conducted a study based on secondary data to assess the Spatial barriers and the bypassing of nearby dental clinics for dental services to calculate the distance patients travel to dental clinics, the rate of bypassing nearby dental clinics and the distance covered when bypassing nearby dental clinics, and explored factors associated with patients' spatial access to dental clinics and found that median distance travelled to a dental clinic was 1.8 km, which is farther for rural (8.4 km) than for urban (1.5 km) patients. It can be assumed that choice of transport option as well as availability of public transport option can be a barrier in seeking regular as well as emergency dental services.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a large catchment zone, majority of the population do not seek adequate dental services provided. Hosung Shin and Han-A Cho [11] conducted a study based on secondary data to assess the Spatial barriers and the bypassing of nearby dental clinics for dental services to calculate the distance patients travel to dental clinics, the rate of bypassing nearby dental clinics and the distance covered when bypassing nearby dental clinics, and explored factors associated with patients' spatial access to dental clinics and found that median distance travelled to a dental clinic was 1.8 km, which is farther for rural (8.4 km) than for urban (1.5 km) patients. It can be assumed that choice of transport option as well as availability of public transport option can be a barrier in seeking regular as well as emergency dental services.…”
Section: Discussionmentioning
confidence: 99%
“…23 These variations make truly defining rurality difficult, especially when considering that a rural area adjacent to a metro or suburban area may have better access to dental services than another area that also meets criteria for rurality. 17 As privately insured individuals are more likely to choose to bypass rural health care for both medical and dental needs, 25,26 a binary measure of rurality may not fully capture the impact of rurality on care outcomes experienced by individuals in more remote rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Marital status was categorized as married or single [ 22 ]. Educational attainment level was classified into three categories: middle school graduation or lower, high school graduation, and college or higher [ 13 , 22 ]. For income, a square root equivalence scale that considered the household’s total earned income, total asset income, and the number of household members for one year was used [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Private dental health insurance and medical aid were dichotomized [ 37 , 38 ]. To check the distribution of dental resources by geographical region, the participant’s living areas were divided into large city districts, small- and medium-sized cities, and rural counties [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation